2011
DOI: 10.3109/01902148.2011.636139
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of rheumatoid arthritis-associated interstitial lung disease in SKG mice

Abstract: Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is associated with increased mortality in up to 10% of patients with rheumatoid arthritis. Lung exposure to cigarette smoke has been implicated in disease development. Little is known about the mechanisms underlying the development of RA-ILD, in part due to the lack of an appropriate mouse model. The objectives of this study were (i) to test the suitability of SKG mice as a model of cellular and fibrotic interstitial pneumonia in the setting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 43 publications
4
55
1
1
Order By: Relevance
“…Our findings are in contrast to two other models of autoimmune arthritis that reported an association with autoimmune arthritis-related inflammation and fibrotic lung disease (34,40,41). These models promoted autoimmune arthritis via different mechanisms, one through altering T-cell signaling with a mutation in zeta chain-associated protein kinase 70 (ZAP-70) (SKG mice), and the other via aberrant MHC Class II expression.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Our findings are in contrast to two other models of autoimmune arthritis that reported an association with autoimmune arthritis-related inflammation and fibrotic lung disease (34,40,41). These models promoted autoimmune arthritis via different mechanisms, one through altering T-cell signaling with a mutation in zeta chain-associated protein kinase 70 (ZAP-70) (SKG mice), and the other via aberrant MHC Class II expression.…”
contrasting
confidence: 54%
“…These data suggest that the lung may be a reservoir for cells inducing arthritis, but not a critical mediator of arthritis pathology. This conclusion is supported by a study of another autoimmune arthritis model that found lung injury alone was not a sufficient stimulus to promote arthritis in susceptible mice, whereas an injection of the fungal b-glucan, zymosan, was sufficient (33,34). Although RA-related lung disease occurs in older adults, we did not find a correlation with age.…”
supporting
confidence: 33%
“…There is also evidence of interstitial lung disease in the zymosaninduced SKG model. Arthritic mice also develop pulmonary fibrosis that is similar to the interstitial lung disease found in some RA patients (Keith et al, 2012). There is limited understanding of whether these additional manifestations are responsive to anti-arthritic treatments and there is scope to further investigate multiple tissue pathology in these models.…”
Section: How Do Animal Models Compare Pathologically To Human Ra?mentioning
confidence: 99%
“…SKG mice, a mutant of the gene encoding ZAP70, spontaneously develop CD4 + T cell-mediated autoimmune arthritis and also develop extra-articular manifestations, including ILD (11,12). For this point, ILD in SKG mice could be a good candidate of a murine CTD-ILD model.…”
mentioning
confidence: 99%